2020
DOI: 10.3389/fphar.2020.01181
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin Possesses Anticonvulsant and Anxiolytic-Like Effects in Murine Animal Models

Abstract: Different types of epilepsy and forms of pathological anxiety have been described as significant neurological disorders that may exist as comorbidities. Some of those disorders share the association of affected limbic areas/neuropathological triggers as well as the use of drugs for their clinical management. The aim of this work was to investigate the anticonvulsant and anxiolytic properties of the vitexin (apigenin-8-Cglucoside), since this compound is a flavonoid usually found as one of the major constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Various mechanisms elucidated by them are like modulation of GABAergic system, controlling the entry of calcium and sodium ions in the cells, and glycine regulation in spinal cord ( Oyemitan et al, 2015 ). Phytomolecules like vitexin ( de Oliveira et al, 2020 ), quercetin ( Nassiri-Asl et al, 2014 ; Nieoczym et al, 2014 ), stigmasterol ( Karim et al, 2021 ), chlorogenic acid ( Aseervatham et al, 2016 ), and ferulic acid ( Hassanzadeh et al, 2017 ) may be responsible for the antiepileptic effect of Alternanthera brasiliana (L.) Kuntze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms elucidated by them are like modulation of GABAergic system, controlling the entry of calcium and sodium ions in the cells, and glycine regulation in spinal cord ( Oyemitan et al, 2015 ). Phytomolecules like vitexin ( de Oliveira et al, 2020 ), quercetin ( Nassiri-Asl et al, 2014 ; Nieoczym et al, 2014 ), stigmasterol ( Karim et al, 2021 ), chlorogenic acid ( Aseervatham et al, 2016 ), and ferulic acid ( Hassanzadeh et al, 2017 ) may be responsible for the antiepileptic effect of Alternanthera brasiliana (L.) Kuntze.…”
Section: Introductionmentioning
confidence: 99%
“…Results were quite significant ( Mondal et al, 2014 ). Phytoconstituents acting on GABA receptors like Ricinoleic acid ( Witt et al, 2002 ), Chlorogenic acid ( Hara et al, 2014 ), p-Coumaric acid ( Scheepens et al, 2014 ), Ferulic acid ( Cheng et al, 2010 ; Sonar et al, 2019 ), Ellagic acid ( Girish et al, 2013 ), Spinasterol ( Socała et al, 2015 ), Stigmasterol ( Karim et al, 2021 ), Acacetin analogs ( Gálvez et al, 2015 ), Vitexin and vitexin analogs ( Zhu et al, 2016 ; de Oliveira et al, 2020 ), and Quercetin and quercetin analogs ( Goutman and Calvo, 2004 ; Kim et al, 2014 ) which were previously been reported from Alternanthera sessilis (L.) R.Br. ex DC., may be behind this GABA receptor mediated central-stimulating activity.…”
Section: Introductionmentioning
confidence: 99%
“…Vitexin and its compounds have been shown to attenuate myocardial ischemia, anticonvulsant and anxiolytic, neuroprotective and many other therapeutic properties [46][47][48][49]. Derivatives and complexes of Quercetin exhibit strong antioxidant activities [50].…”
Section: Metabolic Profiling Of Leafmentioning
confidence: 99%
“…[10,11] Vitexin, an apigenin flavone glucoside, is a key component of several edible and medicinal plants such as pearl millet and chasteberry. [12] It has been reported to exhibit antioxidant, anticonvulsant, antiinflammatory activity, and to regulate neuroinflammation [13,14] and have antidiabetic properties. [15] The lignans yangambin and epiyangambin are found in medicinal plants of several families including the Lauraceae [16] and Asteraceae.…”
Section: Introductionmentioning
confidence: 99%